Using CLIL-Based English Materials Development for Business and Marketing in Vocational High School - Ela Rosyida; Muhammad Burhanuddin Effendy (Journal of English Language Teaching and Learning (JETLE), 2022)
This paper aims to describe the use of Content and Language Integrated Learning (CLIL) approach in developing English language material for Business and Marketing major in vocational high school. It emphasizes on learning a subject and language all at once in language teaching. The study explores the needs of 21st century vocational students, CLIL advantages related to current curriculum, and its material resources. The results offer some relevant theories and considerations in developing the materials to improve students’ English competence on their workplace.